2015
DOI: 10.3382/ps/pev076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in ovo-delivered prebiotics and synbiotics on lymphoid-organs’ morphology in chickens

Abstract: Prebiotics and probiotics, either alone or together (synbiotics), can influence the intestinal microbiota and modulate the immune response. We aimed to investigate the effects of prebiotic and synbiotic administration during the early stage of development on the histological structures of central (bursa of Fabricius and thymus) and peripheral (spleen) lymphatic organs in broilers. We used 800 hatching eggs from meat-type hens (Ross 308). Prebiotics and synbiotics were administered in ovo into the air chamber o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 36 publications
6
70
0
Order By: Relevance
“…lactis or GOS + Lactococcus lactis subsp. cremoris , significantly increased final BWG with unchanged FCE [21]. In another experiment, in ovo injection of GOS and RFO prebiotics alone also increased BWG, but with higher FI and FCE [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…lactis or GOS + Lactococcus lactis subsp. cremoris , significantly increased final BWG with unchanged FCE [21]. In another experiment, in ovo injection of GOS and RFO prebiotics alone also increased BWG, but with higher FI and FCE [42].…”
Section: Discussionmentioning
confidence: 99%
“…Effects of in ovo delivery on microflora-promoting bioactive compounds are detectable during the entire lifespan of the chicken [18,21]. In our previous experiments, we demonstrated that a single injection of prebiotic or synbiotic in ovo could modify the entire spectrum of phenotypic traits in growing broiler chickens, including growth traits [22], immune organ structure and development [13,18,21], histological composition of the intestinal tissue [23,24], parameters of meat quality [25], digestive potency of the pancreas [26], and molecular changes in the cecal tonsils, spleen [17,18], and liver (A. Dunislawska, personal communication).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time (7 th day post hatching), there was a significant depletion of B cells from the bursa of Fabricius in prebiotic and synbiotic-injected chickens (P1, P2, S1 and S2), which suggests the release of the young B cells from primary lymphoid organs and increased colonization of the secondary lymphoid organs (CT) [27]. In 21-day-old chickens, in ovo treatments with synbiotics (S1, S2) resulted in a further increase in B cells (Bu-1 + ) in CT. As for S, in ovo delivery of synbiotics resulted in increased relative S weight on the 21 st day, post hatching [25] and elevated numbers of germinal centers, which are mostly T-independent areas [26]. These findings suggest that synbiotics delivered in ovo stimulate the development of mucosal (GALT) and systemic (spleen) humoral immunity in chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Allantochorion is completely developed and highly vascularized, allowing for transfer of the bioactive solution from air cell to embryonic gastrointestinal tract. This method has been successfully used for prebiotic Bednarczyk et al, 2011) or synbiotic (Maiorano et al, 2012;Slawinska et al, 2014a and2014b;Madej and Bednarczyk, 2016;Madej et al, 2015;Pruszynska-Oszmalek et al, 2015) in ovo delivery. As a consequence, in ovo delivery of prebiotics not only have improved performance traits, such as the growth rate, feed intake (FI), nutrient digestibility (Bednarczyk et al, 2011) and meat quality (Maiorano et al, 2012), but also significantly increased total activity of pancreatic enzymes (amylase, lipase and trypsin) (Pruszynska-Oszmalek et al, 2015) and influence immune system development and function (Slawinska et al, 2014b;Madej and Bednarczyk, 2016;Madej et al, 2015;Plowiec et al, 2015).…”
Section: Introductionmentioning
confidence: 99%